Investing in Renewable Energy and Energy Efficiency in Palestinian Territories: Barriers and Opportunities - Aysar Yasin (Hindawi Limited, 2021)
The main objective of this paper is to identify the renewable energy (RE) and energy efficiency (EE) policy and regulatory risks and barriers in the Palestinian Territories (PT). An accurate insight into the market structure and normative frameworks for RE and EE investments in the PT is performed. For this purpose, a survey has been conducted through two questionnaires and interviews addressed to public decision-makers and local and foreign sectoral companies to study the market confidence in the field of renewable energy sources (RES) and EE. The questionnaire was designed to investigate the attractiveness of RE and EE in the country by directly involving the various market players and to identify what could encourage or hinder investment. RE and EE are, in fact, a valid response to the needs of the PT to guarantee independence and security of supply, ensure access to energy throughout the territory, and reduce emissions. The climate-related issues are listed in the Palestinian political agenda. National subsidies and grants are offered for investment in RES and EE but are still the main barriers. Developments towards further utilization of RES are in progress continually. Marketing campaigns are stimulating the production of RE and EE promotion. RES and EE laws and regulations are continually issued.